Motives and Consequences of Social Network Sites: Teachers in Greece A Case Study - Gougas, Vasileios; Malinova, Lucia (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2021)
the last fifteen years and especially during the pandemic of the COVID-19 virus, there have been an intense In use of Social Network Sites (SNS) by all age, social and professional groups. Logically, that teacher could not escape from this trend. The purpose of this work is to evaluate the hedonic use, utilitarian use, socializing, procrastination, job escapism, work productivity of the specific professional team from the use of SNS. For this reason, a questionnaire consisting of 30 questions was created which was given to a sample of 351 teachers (N=351, Cronbach’s alpha=0.90) in Greece. The results showed that the strongest motivation for the use of SNS is job escapism. It became apparent that the negative effects are associated with escapism and socializing, while hedonic use seems to be more linked with procrastination.